It is equal to -18x^2 +9x
9x
5.4 = (9x+4)/5 - 813.4 = (9x+4)/567 = 9x+463 = 9x7 = xYour answer is 7.
9x+10
9xy2 * 9x5y2 = 81x6y4
( (45) (9x) )
It is equal to -18x^2 +9x
It is: -45x
9x
figure what x is times by 2 do the same with 9 ex v=2 v4-v5=8-5=3
The expression v x 9x can be simplified as 9vx^2. This is the result of multiplying the coefficients (9 and 1) and the variables (v and x) together. The variable x is raised to the power of 2 because there are two instances of x being multiplied together.
-9x + 4 = -50 -9x = -50 - 4 -9x = -54 -x = -6 x = 6.
7
9x
9x+8
Assuming you mean: (9x × x2)2 Then we can say: = (9x3)2 = 81x6
9x + 60 = 375 9x = 315 x = 35